The Integrated Conservation and Tourism Masterplan of Tansen - Aditi Neupane; Arati Bhandari; Lujula Maharjan; Nisham Gaire; Prasanna Paudel; Sonima K.C; Sagun Maharjan (KEC Journal of Science and Engineering, 2025)
The Integrated Conservation and Tourism Masterplan of Tansen is a comprehensive project aimed at preserving the historical, cultural and architectural heritage of Tansen, Palpa, while promoting sustainable tourism and economic growth. Tansen, a historic hill town, is renowned for its unique blend of Newari and Magar cultural influences expressed through its rich tangible and intangible heritage including traditional architecture, religious monuments, vibrant festivals and artisanal crafts. Extensive research, mapping and documentation were conducted to identify Tansen’s key assets and challenges. Guided by the concept "Tansen’s Fading Charm: A Call for Revival," the masterplan seeks to restore Tansen’s identity through heritage conservation, adaptive reuse, and sustainable tourism strategies. The design phase emphasizes the restoration of historical structures such as temples, heritage residence etc. with minimal intervention to preserve authenticity and integrity. In addition, adaptive reuse strategies are employed including converting underutilized buildings into homestays, boutique hotels, craft workshops and community spaces. Innovative public spaces like tudikhel, tin dhara and fulbari is revitalized ensuring community engagement and tourist attraction. The masterplan integrates new infrastructure design with heritage sensitivity, incorporating waste management systems, illumination plans for safety and aesthetics. By combining conservation principles with innovative tourism strategies, the project seeks to provide a comprehensive framework for balancing heritage conservation with modern economic needs, offering a sustainable model for community-driven historical preservation and regional upliftment.